2017
DOI: 10.1016/j.neuint.2017.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Updates to a 13 C metabolic flux analysis model for evaluating energy metabolism in cultured cerebellar granule neurons from neonatal rats

Abstract: A hexose phosphate recycling model previously developed to infer fluxes through the major glucose consuming pathways in cultured cerebellar granule neurons (CGNs) from neonatal rats metabolizing [1,2-13C2]glucose was revised by considering reverse flux through the non-oxidative pentose phosphate pathway (PPP) and symmetrical succinate oxidation within the tricarboxylic acid (TCA) cycle. The model adjusts three flux ratios to effect 13C distribution in the hexose, pentose, and triose phosphate pools, and in TCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Because most postsynaptic spines, many presynaptic varicosities, and some synaptosomes do not have mitochondria, specific neuronal subcellular compartments and functions depend on glycolysis and they would produce and release lactate. Under resting and depolarizing conditions, cultured cerebellar glutamatergic neurons release nearly half of the glucose metabolized to the medium as lactate (216,325,668), as do cultured cortical neurons (378). However, lactate production by cultured cells is quite unlikely to be predictive of cellular sources of lactate in living brain because the large extracellular medium volume dilutes the released lactate and pulls lactate from all cells via the equilibrative LDH and MCT reactions to inflate glycolytic rates (162,274).…”
Section: Strong Evidence Against the Anl Shuttle Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Because most postsynaptic spines, many presynaptic varicosities, and some synaptosomes do not have mitochondria, specific neuronal subcellular compartments and functions depend on glycolysis and they would produce and release lactate. Under resting and depolarizing conditions, cultured cerebellar glutamatergic neurons release nearly half of the glucose metabolized to the medium as lactate (216,325,668), as do cultured cortical neurons (378). However, lactate production by cultured cells is quite unlikely to be predictive of cellular sources of lactate in living brain because the large extracellular medium volume dilutes the released lactate and pulls lactate from all cells via the equilibrative LDH and MCT reactions to inflate glycolytic rates (162,274).…”
Section: Strong Evidence Against the Anl Shuttle Modelmentioning
confidence: 99%
“…Parallel assays showed that lactate oxidation did not increase under these conditions. Cultured cerebellar neurons do oxidize lactate but are highly glycolytic under resting (668) and depolarizing conditions (216,325), with~45% of the glucose consumed being released to the medium as lactate in both cases. The anomaly that astrocyte-neuron shuttling of glycogen-derived lactate should be needed for neurotransmission in cerebellar cocultures when lactate is not used by and is massively released by neuronal monocultures requires explanation.…”
Section: Roles For Glycogen In Neurotransmissionmentioning
confidence: 99%
“…1 and predicts the fractional abundance of 13 C lactate isotopologues (designated M, M1, M2, and M3 lactate, for zero, one, two, or three, respectively, 13 C atoms) for cells metabolizing [1,2- 13 C] glucose as the sole exogenous substrate. Details of this model have been previously described [ 15 , 16 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, it determined that 16% of glucose used by mitochondria comparing to 46% by lactate dehydrogenase ( Gebril et al, 2016 ). By revising bi-directional reaction of the non-oxidative PPP pathway and TCA cycle, this method became more broadly applicable to different cell types ( Jekabsons et al, 2017 ). Patel et al (2021) investigated TCA cycle and neurotransmitter cycle fluxes ratio by FR method from a steady-state [2- 13 C] acetate experiment and the 13 C turnover rates of neurotransmitter by a KFP-like fitting on labeling kinetics of amino acids in 13 C glucose infusion experiment.…”
Section: Application In Neural Cell Researchmentioning
confidence: 99%